Anti-Aging Properties of Plant Stem Cell Extracts - Małgorzata Miastkowska; Elżbieta Sikora (Cosmetics, 2018)
Skin aging is a complex process which involves all the layers of the epidermis and dermis. In order to slow skin aging, methods are researched which would strengthen and protect skin stem cells. Science is in search of the right method to stimulate the proliferation of epidermal stem cells. Plant stem cells show outstanding anti-aging properties, as they can, among other activities, stimulate fibroblasts to synthesise collagen, which, in turn, stimulates skin regeneration. One of the most important agents which give anti-aging properties to plant stem cell extracts is kinetin (6-furfuryladenine). This compound belongs to a cytokine group and is considered to be a strong antioxidant which protects protein and nucleic acids from oxidation and glycoxidation processes. It enables cells to remove the excess of free radicals to protect them from oxidative stress.